Effects of arginine alphaketoglutarate supplementation on body composition and training adaptations - Campbell, B.; Baer, J.; Roberts, M.; Vacanti, T.; Marcello, B.; Thomas, A.; Kerksick, C.; Wilborn, C.; Rohle, D.; Taylor, L.; Rasmussen, C.; Greenwood, M.; et al. (Sports Nutrition Review Journal, 2004)
Arginine-alpha-ketoglutarate (AAKG) has been purported to increase nitric oxide synthesis and thereby enhance blood flow, oxygen delivery, and glucose uptake to muscle leading to greater gains in strength and muscle mass during training. For this reason, nitric oxide stimulating supplements have become a popular supplement among resistance trained athletes. While there is some theoretical rationale as to the potential ergogenic value, the effects of AAKG supplementation during training has yet to be determined. This study examined the effects of AAKG supplementation during training on body composition and training adaptations in experienced resistance trained men (30-50 yrs). METHODS: 35 resistance-trained males (38.9±6 yrs; 178±8 cm, 86±14 kg, 18.8±5% body fat) were matched according to fat free mass and randomly assigned to ingest in a double blind manner supplements containing either a placebo (P) or AAKG (NO2®, MRI, San Francisco, CA). Subjects took 4 grams of the supplements three times daily (12 g/d) for 8-weeks during standardized training. At 0, 4, and 8-weeks, subjects had DEXA body composition determined and performed 1RM bench press, a 50 repetition MVC isokinetic leg extension endurance test, a Wingate 30-s anaerobic capacity test, and a maximal cardiopulmonary exercise test on a treadmill using the Bruce protocol. Data were analyzed by repeated measures ANOVA and are presented as means ± standard deviation changes from baseline for the P and AAKG groups, respectively. RESULTS: No significant differences were observed between groups in changes in body mass (0.33±1.6; 0.82±2.0 kg; p=0.49), fat free mass (0.90±1.4; 0.84±1.1 kg, p=0.79), fat mass (-0.65±1.2; -0.23±1.2 kg, p=0.23), or percent body fat (-0.93±1.3; -0.49±1.2 %, p=0.22). Changes in bench press 1RM (2.6±9; 8.7±7 kg, p=0.03), sprint peak power (-69±192; 78±99 W, p=0.006), time to peak power (-.51±1.3; 0.11±0.35 S, p=0.05), and rate to fatigue (- 3.7±8; 2.7±4.7 W/S, p=0.005) were significantly greater in the AAKG group while no differences were observed in average power (-11±90; 23±50 W, p=0.15) or total work (-334±2,712; 701±1,495 J, p=0.16). No significant differences were observed in isokinetic leg extension peak torque, max repetition total work, time to peak torque, total work, work fatigue, or average power during the muscular endurance test or maximal oxygen uptake. CONCLUSION: Results indicate that AAKG supplementation may augment 1RM strength and sprint power in response to training but does not appear to significantly effect body composition.